Facilitators and barriers to implementing antimicrobial stewardship programs in public South African hospitals - Lodewyk Nicolaas Scheepers; Christina Maria Niesing; Petra Bester (Cambridge University Press, 2023)
Abstract Objective: The South African National Department of Health released guidelines and recommendations for antimicrobial stewardship (AMS) programs to be established in public healthcare facilities. Their implementation remains challenged, especially in North West Province, where the public health system functions under severe strain. This research explored and interpreted the facilitators that strengthen and barriers that hinder the implementation of the national AMS program in public hospitals in North West Province. Design: A qualitative design and interpretive descriptive approach enabled insight into the realities of AMS program implementation. Setting: Public hospitals in North West Province, sampled through criterion sampling (n = 5). Participants: Purposive criterion sampling of healthcare practitioners (n = 30) actively participating in AMS programs in the 5 sampled public hospitals. Method: Qualitative, interpretive description with semi-structured individual interviews that were digitally recorded and transcribed. The ATLAS.ti version 8 software facilitated content analysis, followed by second-level analysis. Results: In total, 4 themes, 13 categories, and 25 subcategories emerged. We detected dissonance between government AMS ideals and the realities of AMS program implementation in public hospitals. A multilevel AMS leadership and governance vacuum exists in a dysfunctional health ecosystem in which AMS must operate. Healthcare practitioners agreed on the importance of AMS despite different understandings of AMS and ineffective multidisciplinary teams. Discipline-specific education and training are essential for all AMS participants. Conclusions: AMS is essential yet complex, and its contextualization and implementation are underestimated in public hospitals. Recommendations are focused on a supportive organizational culture, contextualized AMS program implementation plans, and changes in management.